#TITLE_ALTERNATIVE# - HERISON (NIM 25098007), AHMAD
Waves measurement can be done with pressure sort equipment (Submersible Pressure Transmitter/SPT) and Ultrasonic gauge equipment (Ultrasonic Distance sensor/UDS). SPT equipment is put through the water and UDS is put on the water or in the air (not related to the water). The capability test have been done to both of those equipments, used Wave Gauge equipment type resistance as a references. The test is done to any kind of regular waves and random waves. The measurement result is analyzed to establish wave parameter and still water line (SWL). Generally, in UDS measurement result data, only 23,08% that perfect, whereas perfection in SPT data achieve 89,01%. To both of UDS and SPT, inclination of error more with increase of wave sheer. For SWL measurement comparison UDS with Wave Gauge 98% and relative error point occur is under 1%, whereas measurement comparison SPT with Wave Gauge is 85% and relative error point occur is under 2%. Influence of fluid particle velocity in SPT equipment is so much. It is showed in calculation of regular wave statistic parameter with take into consideration fluid particle velocity, the result is resembling Wave Gauge measurement equipment.